Proceedings of the 38th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2005.244
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Content Management: An Integrated Perspective on Information Management

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
0
4

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 9 publications
1
112
0
4
Order By: Relevance
“…Based on the literature review, it becomes apparent that most studies are ECMS design-oriented in nature, thus proposing methods, standards and frameworks for ECMS adoption and implementation [6,9,10,15,34]. This is in agreement with Vom Brocke et al [12] and Munkvold et al [9] who found that most of the early work on ECMS mainly discusses implementation, adoption and customization of these systems.…”
Section: Literature Review On Ecmssupporting
confidence: 58%
See 4 more Smart Citations
“…Based on the literature review, it becomes apparent that most studies are ECMS design-oriented in nature, thus proposing methods, standards and frameworks for ECMS adoption and implementation [6,9,10,15,34]. This is in agreement with Vom Brocke et al [12] and Munkvold et al [9] who found that most of the early work on ECMS mainly discusses implementation, adoption and customization of these systems.…”
Section: Literature Review On Ecmssupporting
confidence: 58%
“…Although these topics are useful, it does not help practitioners to understand the ways in which ECMS can actually be used in a specific organizational context. However, one exception is a study conducted by Paivarinta and Munkvold [10] that is found to be useful in this regard. In their paper, the authors identify a framework for ECMS implementation and has call for managerial attention.…”
Section: Literature Review On Ecmsmentioning
confidence: 99%
See 3 more Smart Citations